Seeking the diversification benefits with foreign equities and commocities: The case of Polish investor - Radoslaw Kurach (e-Finanse: Financial Internet Quarterly, 2012)
By estimating the correlation coefficients values we compare in this study the diversification potential of the different foreign equity markets and commodities. We present the findings that reflect the perspective of Polish investor. Our results are following: we identify a significant departure from normality in assets returns distributions, hence we provide an evidence on changing correlation patterns, which means varying diversification potential of different assets. We note that commodities are rather moderately correlated with the equity markets and the degree of comovement even diminish if we convert the USD prices into PLN ones. This phenomenon increases the potential for risk reduction of Polish investor.
Keywords: F30; F36; G11; 330; foreign equities; commodities; diversification benefits; Diversifikation; Portfolio-Management; Internationaler Finanzmarkt; Kapitaleinkommen; Polen